Dynamic flavor release from chewing gum: Mechanisms of release. (February 2019) - Hinderink, Emma B.A.; Avison, Shane; Boom, Remko; Bodnár, Igor
Abstract: Dynamic flavor release curves from chewing gum were measured using an Artificial Mouth coupled to the AFFIRM®. A flavor distribution model for chewing gum is proposed, where flavor is present as droplets in both the hydrophilic (water-soluble) and the hydrophobic (water insoluble) parts of the chewing gum and as molecularly dissolved in the hydrophobic part of the gum. During mastication, the flavor droplets in the water-soluble phase are released and responsible for an initial burst release. The flavor droplets captured in the gum-base are pushed towards the interface by mastication and are responsible for the subsequent release. The flavor molecules dissolved in the gum-base, released by diffusion, are only responsible for the release at very long time scales. It was found that the oil-water partition constant is an important parameter to explain the flavor release, where hydrophobic components show slower and longer release, while more hydrophilic components show more burst release. Graphical abstract: Unlabelled Image Highlights: Initial flavor release is primarily induced due to the washing out of the water phase. Flavor release at later times is caused by release of oil + flavor droplets during mastication. Release of flavors through diffusion is negligible. The hydrophobicity of the flavor compound predicts its release from the chewing gum. Less than 4% of the flavor is released during a 15 min mastication period.